2010
DOI: 10.1186/1743-7075-7-18
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin decreased oxidative stress and inflammation and enhanced immune response in humans

Abstract: BackgroundAstaxanthin modulates immune response, inhibits cancer cell growth, reduces bacterial load and gastric inflammation, and protects against UVA-induced oxidative stress in in vitro and rodent models. Similar clinical studies in humans are unavailable. Our objective is to study the action of dietary astaxanthin in modulating immune response, oxidative status and inflammation in young healthy adult female human subjects.MethodsParticipants (averaged 21.5 yr) received 0, 2, or 8 mg astaxanthin (n = 14/die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
365
3
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 465 publications
(382 citation statements)
references
References 34 publications
10
365
3
4
Order By: Relevance
“…Although this CSA gain is smaller than found in RT studies of the elderly (~10%,1, 7, 33, 34), the muscle size gain was one of a suite of changes that accompanied the training stimulus with the AX formulation. This muscle adaptive response has been found with anti‐inflammatory treatments7 and is consistent with the anti‐inflammatory properties reported for AX 10, 11…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although this CSA gain is smaller than found in RT studies of the elderly (~10%,1, 7, 33, 34), the muscle size gain was one of a suite of changes that accompanied the training stimulus with the AX formulation. This muscle adaptive response has been found with anti‐inflammatory treatments7 and is consistent with the anti‐inflammatory properties reported for AX 10, 11…”
Section: Discussionsupporting
confidence: 89%
“…9, 11 The strength gain (14.4%) in the AX formulation group was similar to that found with RT in studies of the elderly (10–15%,1, 7, 33) that used isokinetic or isometric methods to measure MVC. This strength gain was accompanied by an increase in muscle size (2.5%), which indicates that a greater muscle mass was a part of the gains in strength.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Mg 2+ ATPase is believed to be responsible for control of membrane permeability and maintain intracellular Mg 2+ , changes of which can control protein synthesis and cell growth [64]. This study shows significant elevation of these enzyme activities in tissues that may be due to peroxidation of membrane lipids that alters the lipid milieu, leading to alterations in membrane fluidity and cell deformability [65] that indicate the persistent deteriorating effect of BaP in cancer-bearing animals. Kolanjiappan et al [66] had reported elevated Na + K + ATPase activity in erythrocytes of cervical cancer patients and [67] reported elevated activity of Ca 2+ ATPase and Mg 2+ ATPase in BaP induced toxicity of experimental mice.…”
Section: Palanisamy and Samiappanmentioning
confidence: 79%
“…54 Na + /K + -ATPase, a membrane-bound enzyme, is essential to maintain the Na + and K + gradients between the cells and their environment. 55 Ca 2+ -ATPase is of primary importance in control of hydration, volume, nutrient uptake, contractility and excitability of muscles. 56,57 Mg 2+ -ATPase regulates the rate of protein synthesis and cell growth.…”
Section: Discussionmentioning
confidence: 99%